Influence of 0.2 minimum alveolar concentration of enflurane on the ventilatory response to sustained hypoxia in humans. - Nagyova, B; Dorrington, K; Poulin, M; Robbins, P (1997)
To determine the influence of 0.2 minimum alveolar concentration (MAC) of enflurane on the time course of ventilation during sustained hypoxia, we studied 10 healthy adult volunteers with and without enflurane. The following design was used: end-tidal Po2 was maintained at 13.3 kPa for 8 min, at 6.7 kPa for 20 min and at 13.3 kPa for 8 min. End-tidal Pco2 was held constant throughout at 0.67 kPa above the subject's natural value. Control experiments were conducted with no hypoxia imposed. During the experiment subjects breathed via a mouthpiece from an automated gas mixing system which controlled end-tidal values. Enflurane reduced baseline (euoxic) ventilation from 20.9 (SEM 2.0) litre min-1 to 10.1 (1.0) litre min-1 (ANOVA, P < 0.001). Enflurane reduced the acute ventilatory response to hypoxia (AHVR) from 20.1 (3.3) litre min-1 to 5.0 (1.3) litre min-1 (ANOVA, P < 0.01), and the ventilatory off-response at cessation of hypoxia from 11.7 (2.4) litre min-1 to 1.8 (0.5) litre min-1 (ANOVA, P < 0.02). There was no significant difference in hypoxic ventilatory decline (HVD) without and with enflurane (8.9 (2.4) litre min-1 vs 5.5 (1.1) litre min-1; ANOVA, ns). These results confirm that 0.2 MAC of enflurane suppressed the acute ventilatory response to hypoxia, but had no significant effect on the subsequent ventilatory decline during sustained hypoxia.